Purification and characterization of the staphylococcal slime-associated antigen and its occurrence among Staphylococcus epidermis clinical isolates. - Baldassarri, L (1996)
The Staphylococcus epidermidis slime-associated antigen (SAA) was purified and characterized. N-Acetyl-glucosamine accounted for 70% of the dry weight of SAA, which was immunolocalized on the ruthenium red-positive material produced by slime-positive strains. A total of 59% of slime-producing S. epidermidis clinical isolates expressed SAA, while the phenotype slime- SAA+ was never recovered.